Fiscal and monetary response to the COVID-19 pandemic in India. Issue 1 (2nd November 2020) - Jose, Justina; Mishra, Priyanka; Pathak, Rahul
Abstract : Purpose: This article examines the preliminary impact of the Sars-CoV-2 pandemic on India's economic and budgetary landscape – the most affected developing country from the first wave of the pandemic. It also includes a discussion of the monetary and fiscal responses adopted and the challenges faced in formulating the response to the pandemic. Design/methodology/approach: Using high-frequency economic and fiscal indicators, this article evaluates the economic impact of the pandemic on the Indian economy. Further, it uses data from government sources and news to highlight the measures adopted at the national and subnational level in response to the pandemic. Findings: The difficult economic conditions prior to the pandemic limited the fiscal space available to the government. As a result, the national and subnational governments have been cautious of accumulating excessive debt and have primarily responded with liquidity-enhancing measures, in addition to some fiscal measures for the most vulnerable. Overdependence on consumption taxes has led to unprecedented revenue shortfalls prompting the exploration of new avenues for revenue generation and implementation of austerity measures – some of which may be counterproductive in the long run. Originality/value: The paper highlights the policy response of the largest democracy that has been hit hard by the pandemic. It also highlights various institutional and resource constraints that influenced the policies adopted. India's experience in responding to the virus could provide lessons for other developing countries.